TRADISI MIPIT PARE DI KASEPUHAN CIPTAGELAR - Aini, Siti Noor; Syafi?, Moh. (IAIN Tulungagung, 2019)
Kasepuhan Ciptagelar is an indigenous community living in the Mount Halimun area, Salak, Sukabumi, West Java. The Ciptagelar community still maintains the tradition of Karuhun, the Mipit Pare ritual. Mipit Pare is a unique procession carried out towards the rice harvest season. The Mipit Pare ritual is carried out by the Ciptagelar customary community as a form of communication with Karuhun so that the harvest is abundant. The form of communication that is formed is quite complex, in which there are certain communication events and typical actions. As a society with rice culture, all forms of rice-related activities are accompanied by certain rituals. This study uses a qualitative method with an ethnographic approach to communication, which focuses on communication activities that occur during the Mipit Pare ritual. The act of communication is a single interaction function, such as statements, requests, orders or non-verbal behavior. This study shows that the Mipit Pare tradition in the Ciptagelar indigenous community has its own characteristics, either in the form of vertical communication (humans with Karuhun and God) or horizontal communication (humans with humans and the surrounding environment). Keywords: Ciptagelar, Mipit Pare, rice culture, ethnography communication.